2019
DOI: 10.31383/ga.vol3iss1pp71-76
|View full text |Cite
|
Sign up to set email alerts
|

Validation of CRC and NSCLC somatic mutations detected by NGS using ddPCR

Abstract: Next Generation Sequencing (NGS) has become powerful tool in molecular oncology. It allows multiparallel targeted sequencing that enables comprehensive assessment of tumor heterogeneity. Detection of mutations in colorectal cancer (CRC) and non-small cell lung cancer (NSCLC) defines patients diagnosis, therapy and prognosis. Multiple genes, their somatic mutations to be precise, carry different degrees of importance for any of these stages. Ion AmpliSeq™ Colon and Lung Cancer Research Panel v2, which was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In 2019, Salihefendić et al [ 5 ] studied whether ddPCR technology could be used as a confirmatory method for the detection and quantification of somatic mutations, previously detected by NGS. A total of 35 samples from CRC and NSCLC patients were analyzed, and the results showed that there were no statistically significant differences between the results obtained by NGS and ddPCR methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2019, Salihefendić et al [ 5 ] studied whether ddPCR technology could be used as a confirmatory method for the detection and quantification of somatic mutations, previously detected by NGS. A total of 35 samples from CRC and NSCLC patients were analyzed, and the results showed that there were no statistically significant differences between the results obtained by NGS and ddPCR methods.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 35 samples from CRC and NSCLC patients were analyzed, and the results showed that there were no statistically significant differences between the results obtained by NGS and ddPCR methods. Therefore, high sensitivity and resolution of ddPCR, make it an adequate method for validating low-frequency somatic mutations [ 5 ] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations